PENGARUH AUDIT MANAJEMEN TERHADAP KINERJA KARYAWAN PADA PT BANK PANIN TBK CABANG KENDARI - Septianingrum, Elisa (JURNAL AKUNTANSI, 2016)
This research aims to examine the effect of management audit on employee performance at PT. Bank Panin Tbk Kendari. The primary data is taken from perceptions of Internal Control Unit at PT. Bank Panin Tbk Kendari. The perceptions of respondents are obtained through questionnaire using ordinal measure with 5 points likert scale. The statistical method employed to test each hypothesis is simple regression analysis. The result shows that management audit has a significant effect on the employee performance. Regression result of Adjusted R Square coefficient is 0.763 or 76.3%. The rest is 23.7% explained by other variables which are not examined. This finding has proven that management audit must be done by the entire banking companies, especially by PT. Bank Panin Tbk Kendari, in order to achieve a better employee performance. Keywords: Management Audit and Employee Performance.